Features of Syntagmatic Associations for Stimuli-Names of Food Products in Ukrainian and Modern Greek Languages - Petrova, Galyna (Lesya Ukrainka Eastern European National University, 2017)
500 respondents who are Ukrainian native speakers and 100 Modern Greek speakers participated in free word association test held in March and July, 2015 in Kyiv, Ukraine, and in Athens, Greece. The data were calculated as to the frequency of responses and composed a field of associations for each stimulus. The classification of associations to the word-stimuli “food products” was based on existing classifications and on the specific of the test material. In this paper, the authors discuss the syntagmatic type of associations expressed by adjectives that represent the objective characteristics of the product and form a phrase with a word-stimulus (Terekhova, 2000). They can be roughly divided into 2 groups of associating directions: features of product attributes (52 % of all syntagmatic associations in Ukrainian language (hereinafter – UL) and 41% in Modern Greek (hereinafter – MGL)) and feautures of stages that the product passes (UL – 41%, MGL – 48 %). Some differences in quantitative and qualitative aspects were found during the determination of associating directions within the syntagmatic type of associations: different percentage of responses in associating directions in quantitative aspect. As to the quality, the differences lay in determination of feature directions in the languages. Thus for the associative field of Modern Greek language, the reactions that characterize the form of the product have not been found at this stage yet. У статті подано результати аналізу матеріалів вільного асоціативного експерименту: репрезентовано спробу класифікації асоц іацій на стимули-назви продуктів харчування в українській та новогрецькій мовах; подано опис одного з найбільших за обсягом – синтагматичного типу асоціацій; визначено його підтипи та подальше розгалуження; виявлено загальні та специфічні риси мовної свідомості українців та греків. у межах класифікації асоціацій на позначення продуктів харчування вагоме місце за обсягом реакцій займають синтагматичні асоціації. Під час визначення напрямів асоціювання в межах синтагматичного типу асоціацій виявлено розбіжності в кількісному та якісному аспектах. У кількісному аспекті різниться відсоткове співвідношення реакцій у напрямах асоціювання. У якісному – відмінності полягають у визначенні підгруп характеристик у різних мовах, так зокрема в асоціативному полі новогрецької мови на цьому етапі дослідження не виявлено реакцій, що є характеристиками форми продукту.
Keywords: асоціативне поле; вільний асоціативний експеримент; синтагматичні асоціації; напрямок асоціювання; реакція; стимул; типи асоціацій; associative field; free association test; syntagmatic associations; ways of associating; response; stimulus; types of associations